Advances in cancer imaging require renewed radiotherapy dose and target volume concepts. (July 2020) - Kaanders, Johannes H.A.M.; van den Bosch, Sven; Dijkema, Tim; Al-Mamgani, Abrahim; Raaijmakers, Cornelis P.J.; Vogel, Wouter V.
Abstract: Advances in diagnostic imaging create opportunities for improved therapeutic targeting of cancer but conceptual thinking about radiotherapy target volume definition and dose-prescription is not keeping up. In this opinion paper we discuss how modern imaging can contribute to new concepts for radiotherapy dose-prescription and target volume definition illustrated by the example of head and neck cancer. These new insights have the potential to significantly reduce radiation associated toxicity and may have important impact on the combination of radiotherapy with systemic cancer therapies.